Biomass production of different grass species available at irrigated lowland of Dassench Woreda in South Western Ethiopia - Hidosa, D; Hitiso, W; Guyo, M (Bangladesh Journal of Animal Science, 2018)
On farm adaptability test of different grass species was conducted on pastoral area of Keelewe peasant association in Dassench Woreda of South Omo Zone in 2016 under irrigated condition with the objective to identify high biomass yielding grass species. The field experiment was laid out in a Randomized Complete Block Design with four replicates per tested species. The tested grass species were Chloris gayana, Cenchrus ciliaris and Panicum colaratum. The result indicated that there was a significant difference (p>0.05) among the tested grass species. Panicum colaratum yields the highest (18.08 t/ha) than the Chloris gayana (15.21 t/ha) whereas, Cenchrus ciliaris had yielded the lowest dry matter yield (11.20t/ha) than Chloris gayana and Panicum colaratum. The Panicum colaratum was one with maximum dry matter yield being recommended for irrigated conditions in the study area. However, further testing is required on feeding value, dry matter yield under different fertilizer dose, stem height, leaf to stem ratio, irrigation requirements and chemical composition of tested grass species. Bang. J. Anim. Sci. 2017. 46 (3): 188-191